(untitled) (Annals of the University of Bucharest. Philosophy Series, 2024)
The article aims to pay aesthetic and axiological tribute to Charles Fourier’s conception of the so-called attraction passionelle – the basic drive of social development, and, in particular, of the composite passion, “the most beautiful of the twelve passions, the one which enhances the value of all the others”. The exposition will consecutively focus on Herbert Marcuse’s note in Eros and Civilization on the transformation of labor into pleasure as the central idea of Fourier’s socialist utopia; on Fourier’s insisting that only the composite passions, not the simple, are human trait; and, respectively, on analyzing beyond Fourier and Marcuse the role and significance of the composite passion – or, the “pure human passion”, as the base of creativity in contemporary culture of post-/trans-/alter-human art, science and technology. Last but not least, the exposition will pay attention to how this “pure human passion” as the core of creativity could be related to the emotional intelligence – artificial intelligence (EI vs. AI) opposition in contemporary age.